ENHANCEMENT OF BIOETHANOL FUEL PROPERTIES FROM CIU GUMAYUN THROUGH ADSORPTIVE DISTILLATION WITH NATURAL ZEOLITE AND SILICA GEL - Farid Majedi; Galih Satrio; M. Shafwallah Al Aziz R. (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Bioethanol as an alternative energy source for fossil energy conversion. A potential source of bioethanol is Ciu Gumayun, a liquor with 25% alcohol content, which can be purified through adsorptive distillation using natural zeolite and silica gel as water adsorbents. The study aimed to determine the effects of adsorbent variations on the alcohol, water, and calorific value of bioethanol using a multistage adsorptive distillation process at 78°C with 2 liters of Ciu and 70 grams of adsorbent in each distillate. The results of the natural zeolite adsorption distillate: alcohol content of 67%, 79%, 88%, and 92%, with a final volume of 162 ml. In the silica gel adsorption distillate, alcohol content: 68%, 79%, 86% and 92%, with a final volume of 170 ml. The water content of both natural zeolite and silica gel distillates was 8%, with water volumes of 12.96 ml for natural zeolite distillate and 13.6 ml for silica gel distillate. The calorific value was 24,147 J/g for natural zeolite distillate and 24,704 J/g for silica gel distillate. From the alcohol content, water content, and calorific value, silica gel proved to be more effective in the adsorptive distillation process.